What factors shape the liquidity levels of euro area sovereign bonds? - Linas Jurksas (Open Economics, 2018)
The purpose of this paper is to determine the factors that shape the liquidity levels of euro area sovereign bonds. The values of liquidity measure and explanatory variables were calculated from the limitorder book dataset for almost five hundred bonds from six largest euro area sovereign bond markets. The created variables were used in a cross-sectional regression model. The results revealed that characteristics of sovereign bonds are indeed highly linked with bond liquidity levels, and these effects become even stronger during the regimes of lower market liquidity. Contrary to the statements of market participants and findings of many other studies, the magnitude of trading automation and obligatory requirements imposed on dealers were found to be negatively linked with the liquidity level of sovereign bonds.
Keywords: C21; G12; G14; G21; 330; bond characteristics; cross-sectional regression; liquidity level; sovereign bonds; trading features